Late Pliocene benthic δ¹³C and δ¹⁸O from ODP Site 959 and δ13C from ODP Site 662 in the eastern equatorial Atlantic - van der Weijst, Carolien; Winkelhorst, Josse; Lourens, Lucas Joost; Raymo, Maureen E; Sangiorgi, Francesca; Sluijs, Appy (PANGAEA, 2020)
We present high-resolution late Pliocene (~2.7-3.5 Ma) benthic foraminiferal stable isotope records from eastern equatorial Atlantic ODP Site 959 (δ^13^C and δ^18^O) and ODP Site 662 (δ^13^C). The complementary δ^18^O record from Site 662 was published in Lisiecki and Raymo (2005; doi:10.1029/2004PA001071). Site 959 data was generated using the epibenthic species Cibicides wuellerstorfi and stable isotope analysis was performed at Utrecht University in 2016 on either a Thermo-Finnigan Kiel III automated preparation system coupled to a Thermo-Finnigan MAT 253 mass spectrometer, or a Thermo Finnigan GasBench-II carbonate preparation device coupled to a Thermo Finnigan Delta-V mass spectrometer. Site 662 data was generated using Cibicides wuellerstorfi when possible, and alternatively, a combination of Cibicides species (Cibicides spp.) was used. Stable isotope analysis was performed in the early 1990s at Massachusetts Institute of Technology using a VG Prism mass spectrometer. These new records are combined with previously published benthic δ¹³C and δ¹⁸O records. By assuming that both δ¹³C and δ¹⁸O behave as conservative tracers, we estimate the isotopic end-members of deep Atlantic water masses. At least three endmembers are needed to explain the spatial δ¹³C-δ¹⁸O variability in the deep North Atlantic Ocean: two Northern Component Water (NCW) and one Southern Component Water (SCW) water masses. We use a ternary mixing model to quantify the mixing proportions between SCW and NCW in the deep Atlantic ocean.
Keywords: Benthic isotopes; Cibicides; Eastern Equatorial Atlantic; ODP Site 662; ODP Site 959; δ13C; δ18O